Novel sulfate tablet PBK‐1701TC versus oral sulfate solution for colon cleansing: A randomized phase 3 trial. Issue 1 (7th October 2019) - Yang, Hyo‐Joon; Park, Dong Il; Park, Soo‐Kyung; Lee, Chang Kyun; Kim, Hyo Jong; Oh, Shin Ju; Moon, Jung Rock; Lee, Beom Jae; Koh, Jin Sung; Kim, Hyun Soo; Park, Seon‐Young; Kim, Dong Hyun; et al.
Abstract: Background and Aim: PBK‐1701TC is a novel sulfate tablet‐based that contains 320 mg of simethicone and delivers 90% of the salt and water delivered by oral sulfate solution (OSS) preparation. This study evaluated the efficacy, safety, and tolerability of PBK‐1701TC compared with OSS in bowel preparation for colonoscopy. Methods: This randomized, multicenter, phase 3 non‐inferiority trial included adults aged 19 years or older with a body mass index of 19–30 kg/m 2 undergoing colonoscopy at five university hospitals in Korea. The primary efficacy endpoint was successful bowel‐cleansing rate, defined as Harefield Cleansing Scale grade A or B as evaluated by blinded central readers. Secondary endpoints included the presence of residual air bubbles. Adverse events and laboratory evaluations were monitored to assess safety. Tolerability was assessed via participant interview. Results: Overall, 235 participants were randomized, and 224 were included in the per‐protocol analysis (PBK, 112; OSS, 112). Successful bowel cleansing was achieved for 95.5% (107/112) in the PBK group, which was non‐inferior to the OSS group (98.2%, 110/112) with a difference of −2.7% (one sided 97.5% confidence limit, −8.1%). The participants in the PBK group had fewer intraluminal bubbles (0.9% vs 81.3%, P < 0.001) and reported a lower incidence of nausea and vomiting, with better acceptance, taste, and willingness to repeat the regimen than those in the OSS group (all P < 0.05). Conclusion: The novel sulfate tablet, PBK‐1701TC, was non‐inferior to OSS with respect to bowel‐cleansing efficacy and exhibited better safety and tolerability in adults undergoing colonoscopy.